An inflation-based maintenance profitability model (2008)
The maintenance profitability problem is an important but emerging concept of maintenance performance measurement that views the maintenance function as a value adding subsection of the organisation. The service provided by the maintenance system to production is charged as a price, which results in the monetary contribution of the maintenance department to the organisation. In the same way, as production would add financial benefits to the organisation the maintenance system is portrayed as adding profit to the organisation. In this work, we present a mathematical model that calculates the maintenance profitability of an organisation under the condition of inflation using a composite mathematical function. It is concluded that viewing maintenance from a profit-making orientation provides a challenge to the maintenance team, thus driving them towards improved performance.